COMPARISON OF CONDUCT DISORDER AND HYPERKINETIC CONDUCT DISORDER : A RETROSPECTIVE CLINIAL STUDY FROM NORTH INDIA - Malhotra, Savita (Medknow Publications, 1999)
In a retrospective descriptive study of hyperkinetic conduct disorders (HCD) and conduct disorders (CD), as per ICD-10 diagnostic criteria, their clinical and phenomenological correlates were compared; with an aim of describing their distinctive clinical profiles. 20 cases of HCD and 25 cases of CD were compared on socio-demographic variables, temperament and specified clinical variables. The two groups differed in terms of the HCD group having younger age of onset, a more gradual development of and longer duration of conduct symptoms as compared to CD children. HCD children also had temperamental deviance (in the form of inattention, distractibility), lower IQ, more perinatal complications and delayed milestones as compared to the CD group; which made significant contribution to discriminant functions between the two groups. Results point towards different pathways of development of conduct symptomatology in HCD group as compared to the CD group